2024
DOI: 10.1038/s41556-024-01367-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways drive anterior hypoblast specification in the implanting human embryo

Bailey A. T. Weatherbee,
Antonia Weberling,
Carlos W. Gantner
et al.

Abstract: Development requires coordinated interactions between the epiblast, which generates the embryo proper; the trophectoderm, which generates the placenta; and the hypoblast, which forms both the anterior signalling centre and the yolk sac. These interactions remain poorly understood in human embryogenesis because mechanistic studies have only recently become possible. Here we examine signalling interactions post-implantation using human embryos and stem cell models of the epiblast and hypoblast. We find anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…However, a different antibody was used to detect pSMAD1/5/9 in preimplantation embryos in Reyes de Model et al (2015) . The source of antibody that was used to detect pSMAD1/5/9 in blastocysts in Graham et al (2014) was not described in detail, but a more recent study from the same lab reported absence of pSMAD1/5/9 in the blastocyst using the same antibody that we used ( Weatherbee et al, 2024 ). Ours is the only study to confirm pSMAD1/5/9 specificity in Bmp4 null blastocysts, providing strong evidence for antibody specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a different antibody was used to detect pSMAD1/5/9 in preimplantation embryos in Reyes de Model et al (2015) . The source of antibody that was used to detect pSMAD1/5/9 in blastocysts in Graham et al (2014) was not described in detail, but a more recent study from the same lab reported absence of pSMAD1/5/9 in the blastocyst using the same antibody that we used ( Weatherbee et al, 2024 ). Ours is the only study to confirm pSMAD1/5/9 specificity in Bmp4 null blastocysts, providing strong evidence for antibody specificity.…”
Section: Discussionmentioning
confidence: 99%